Population Structure Characteristics and Survival Status of Natural Platycladus Orientalis in Loess Hilly Region - Sun Ting; Li Gangtie; Ma Yunxia; Song Jiajia; Guo Jingjie; Gu Zhonghou; Liu Kun; Li Zhilong; Li Min (Shuitu baochi tongbao)
[Objective] Population structure characteristics and survival status of natural Platycladus orientalis in the loess hilly region were determined in order to provide a scientific basis for high-quality and sustainable development of forest grassland in this area. [Methods] Characteristics were quantitatively analyzed by using a dynamic change index based on a static life table combined with spectral analysis on the time scale and time series simulation prediction to carry out a comprehensive survival analysis of this cypress species. [Results] ① The height, crown width, and diameter structure of the P. orientalis population indicated that young trees were abundant. ② The survival curve of the P. orientalis population was close to Deevey-Ⅱ type, and the population was sensitive to external interference. ③ Population dynamics were characterized by strong viability in the early stage, stable growth in the middle stage, and decline in viability in the later stage. Time series simulation and prediction analysis showed that the population of P. orientalis showed different degrees of increasing trend and strong growth recovery ability. [Conclusion] The natural population structure of P. orientalis in the loess hilly region was stable and growing, and the survival curve was close to that of Deevey-Ⅱ type.